(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The purpose of the study is to analyze the political situation in Syria during the ALahed AL Fusaily by addressing of Al- Asma newspaper (1919-1920), in addition to Prince Faisal’s role internally and externally during the Peace Conference in 1920, And the unity of the States of the Levant, to be the basis for the launch of a wider Arab unity, and the statement of conspiracy allies on the Arabs, especially France and its attempts to occupy Syria, and then efforts by the Syrian Arab state to prevent this, and also briefly discussed Prince Faisal talks and meetings and correspondence with the British government from Hand and To the governments and political and popular bodies in Syria, Lebanon and Palestine on the other hand, which revolves around ways to achieve the unity of the countries of the Levant, and then review the role of the Syrian press in the history of modern Arabs in general and Syrian history in particular, where appeared in the early twentieth century newspapers in Arabic, In the Arab nationalist thought, as a result of which was persecuted by the Ottoman Empire, and then the French mandate.